Endophytic fungi related to the ash dieback causal agent encode signatures of pathogenicity on European ash - Maryam Rafiqi; Chatchai Kosawang; Jessica A. Peers; Lukas Jelonek; Hélène Yvanne; Mark McMullan; Lene R. Nielsen (IMA Fungus)
Abstract Tree diseases constitute a significant threat to biodiversity worldwide. Pathogen discovery in natural habitats is of vital importance to understanding current and future threats and prioritising efforts towards developing disease management strategies. Ash dieback is a fungal disease of major conservational concern that is infecting common ash trees, Fraxinus excelsior, in Europe. The disease is caused by a non-native fungal pathogen, Hymenoscyphus fraxineus. Other dieback causing-species have not previously been identified in the genus Hymenoscyphus. Here, we discover the pathogenicity potential of two newly identified related species of Asian origin, H. koreanus and H. occultus, and one Europe-native related species, H. albidus. We sequence the genomes of all three Hymenoscyphus species and compare them to that of H. fraxineus. Phylogenetic analysis of core eukaryotic genes identified H. albidus and H. koreanus as sister species, whilst H. occultus diverged prior to these and H. fraxineus. All four Hymenoscyphus genomes are of comparable size (55–62 Mbp) and GC contents (42–44%) and encode for polymorphic secretomes. Surprisingly, 1133 predicted secreted proteins are shared between the ash dieback pathogen H. fraxineus and the three related Hymenoscyphus endophytes. Amongst shared secreted proteins are cell death-inducing effector candidates, such as necrosis, and ethylene-inducing peptide 1-like proteins, Nep1-like proteins, that are upregulated during in planta growth of all Hymenoscyphus species. Indeed, pathogenicity tests showed that all four related Hymenoscyphus species develop pathogenic growth on European ash stems, with native H. albidus being the least virulent. Our results identify the threat Hymenoscypohus species pose to the survival of European ash trees, and highlight the importance of promoting pathogen surveillance in environmental landscapes. Identifying new pathogens and including them in the screening for durable immunity of common ash trees is key to the long-term survival of ash in Europe.